Set theory for physicists - Pereyra, Nicolas A. (IOP (Series). Release 6., 2019)
This book gives a rigorous, physics focused, introduction to set theory that is geared towards natural science majors. We present the science major with a robust introduction to set theory, focusing on the specific knowledge and skills that will unavoidably be needed in calculus topics and natural science topics in general, rather than taking a philosophical-math-fundamental oriented approach that is commonly found in set theory textbooks.